A SURPRISING DISCOVERY: UNUSUAL FOREIGN BODIES FOUND IN THE GIZZARD OF THE INDIAN BLUE ROCK PIGEON, COLUMBA LIVIA LINNAEUS 1758 – A COMPREHENSIVE OVERVIEW - Chittora, R.K; Jadhav, A.S.; Upreti, N.C (International Journal of Allied Sciences (IJAS), 2022)
The Animal Rahat Solapur team conducted the examination following standard protocols and in daylight conditions. As they examined the pigeon’s visceral organs, they stumbled upon a peculiar discovery within the gizzard. Upon closer inspection, the cross-section of the gizzard revealed small diamond-shaped hard plastic bodies, plastic beads, and disc-shaped plastic material, in addition to a number of small-sized grits. This case brings to light the presence of unusual foreign bodies within the gizzard of the Indian Rock Pigeon (Columba livia) and opens the door for further investigation into the implications of such findings